2011
DOI: 10.1111/j.1600-6143.2010.03414.x
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Donor-Specific HLA Antibodies in Rejection and Ductopenia Development in ABO Compatible Liver Transplantation

Abstract: The role of humoral alloreactivity in ABO-compatible liver transplantation remains unclear. To understand the significance of donor-specific HLA alloantibodies (DSA) in liver rejection, we applied the currently used strategy for detection of antibody-mediated rejection of other solid allografts. For this purpose we reviewed the data on 43 recipients of ABO identical/compatible donor livers who had indication liver biopsy stained for complement element C4d and contemporaneous circulating DSA determination. Seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
163
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(182 citation statements)
references
References 52 publications
15
163
1
1
Order By: Relevance
“…Consequently, it is reasonable to hypothesize that, given the nature of the procedure, DDLT recipients may be more sensitive to the detrimental effects of HLA antibodies in comparison to LDLT recipients. That said, similar to recent reports, DSA is likely to have an impact in both donor settings because our multivariate analysis demonstrated an independent association between DSA and graft failure regardless of donor type (5)(6)(7)(8)10,(19)(20)(21).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consequently, it is reasonable to hypothesize that, given the nature of the procedure, DDLT recipients may be more sensitive to the detrimental effects of HLA antibodies in comparison to LDLT recipients. That said, similar to recent reports, DSA is likely to have an impact in both donor settings because our multivariate analysis demonstrated an independent association between DSA and graft failure regardless of donor type (5)(6)(7)(8)10,(19)(20)(21).…”
Section: Discussionsupporting
confidence: 91%
“…Although early studies suggested correlations between positive crossmatches and graft loss in LT, liver recipients have been routinely transplanted without regard for HLA antibodies for years (1,25). Not until the recent seminal work of multiple investigators has the interest in alloantibodies in LT become reinvigorated (6,7,10,20,26,27). Significant associations have been made between preformed and de novo DSA and liver transplant rejection, alloimmune hepatitis and patient and graft survival (4)(5)(6)(7)(8)(9)(10)19,21,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antibody-mediated injury may coincide with, or augment, bouts of acute cellular rejection with positive donor-specific antibodies and C4d staining observed in roughly 50% of specimens exhibiting cellular rejection (12-19 of 28, depending on pattern). 92 Other studies have shown C4d staining with many other allograft abnormalities not related to rejection, including chronic hepatitis, vascular injury, or bile duct injury. 84,95,97 Therefore, C4d staining should be interpreted with caution and has no particular significance without the correct clinical context and congruent histopathologic changes in the biopsy.…”
Section: Livermentioning
confidence: 98%
“…84,85 Within the population of ABO-compatible grafts, recipients with known, preformed lymphocytotoxic antibodies to the donor (positive cross-matches) are at higher risk for developing ABMR, 86-90 whereas cross-match-negative transplants appear to have minimal risk of isolated ABMR. 89,91,92 In this context, unlike heart or kidney, the diagnosis of isolated ABMR in liver is rare and one of exclusion. Diagnostic criteria are not as well established compared with other solid organ transplants, but histopathologic changes suggesting ABMR (see Table 1), C4d immunostaining, and donor-specific antibody detection should all be combined to evaluate for the possibility of ABMR.…”
Section: Livermentioning
confidence: 99%